Serum CRP interacts with SPARC and regulate immune response in severe cases of COVID-19 infection - Liu, Chengyang; Zheng, Chenyang; Shen, Xipeng; Liang, Ling; Li, Qiuyu (Frontiers in Immunology, 2023)
This article investigates the relationship between serum C-reactive protein (CRP) levels and circulating megakaryocyte proportion in COVID-19 patients and their potential role in virus response and immune regulation. The study found that serum CRP levels correlate with megakaryocyte marker genes in COVID-19 infection, and megakaryocytes were significantly accumulated in severe cases. The authors also proposed a model of how CRP regulates immune responses in COVID-19 infection, suggesting that the impact of CRP on megakaryocytes may partly rely on the secreted protein acidic and rich in cysteine (SPARC) expressed by megakaryocytes. The study highlights the complex interplay between inflammatory markers, megakaryocytes, and immune regulation in COVID-19 and sheds light on potential therapeutic targets. However, further investigations are needed to establish a causal relationship and elucidate the underlying mechanisms.